Aberrant DNA Methylation in Human Hepatocellular Carcinoma - Rizma Khan; Umaira Zakir; Faizan- (ziauddin University, 2024)
Essential epigenetic mechanism i.e., DNA methylation in humans is being continuously acknowledged as a hallmark of various cancer. Hypo-methylation and CpG hyper methylation considered early events in cancer development hence; their understanding will provide us new tools for diagnosis. Hypo-methylation of repetitive sequences associated with genomic instability and may cause changes in the local chromatin environment and disrupt gene expression that contributes to carcinoma development. Additionally, hyper methylation of the promoter region of genes, including p15, p16, RASSF1A, accumulates during cancer development, which can influence the process of angiogenesis, DNA repair, regulation of cell cycle, apoptosis as well as tumour cell invasion. The methylation process mediated via DNA methyltransferases; hence, the variation in these enzymes may lead to hepatocellular carcinoma (HCC). Oncogenes activation and tumour suppressor genes inactivation during the growth and development of HCC, promotor hyper-methylation and hypo-methylation are the activaters. This review summarized recent DNA methylation information and role of aberrant methylation in cancer progression by using different research papers from NCBI between 2016-2020, that would be helpful in the diagnosis and treatment of hepatocellular carcinoma.  Keywords: DNA Methylation; CpG Island; Gene Expression; Hypo-Methylation; Hyper- Methylation; Review.